The Land use changes in the Jfara region during the period 1986-2013 (Al Zahraa area) (Journal of Libya for geographical studies, 2025)
The study aimed to identify and analyses the changes of vegetation patterns and their changes in (Al-Zahraa area) during 1986-2013 using remote sensing technology and information systems. To achieve the aim of the study satellite images were used also to analyses the vegetation cover of the area and the changes that occurred. The study found clear changes in the land uses, as land uses diversified into urban uses, agricultural uses, natural plants, forests, and barren lands. The study also showed a clear and rapid expansion of urban uses at the expense of other land uses, as it was about 1694 hectares in 1986 and then became (5471) hectares in 2013. The ​​agricultural lands, was (5482) hectares in 1986 and then decreased in 2013 to become only (3312) hectares, while the area of ​​natural plants in the area decreased by 22%. The study also showed that the forest area in the Zahraa area has decreased significantly, losing 82% of its area. The study recommended the necessity of preserving the vegetation cover in the region by increasing the cultivation and reclamation of lands, expanding the planting of trees to resist desertification, regulating grazing within agricultural lands, and encouraging research and studies concerned with these problems.
Keywords: Vegetation cover; urban uses; agricultural uses; forests; remote sensing